Influence of intrinsic and extrinsic food attributes on consumers' acceptance of reformulated food products: A systematic review - Bolha Anja; Blaznik Urška; Korošec Mojca (Sciendo, 2020)
Reducing the salt, sugar and fat content of food is recognised worldwide as one of the strategies available for reducing the incidence of obesity and non-communicable diseases. The food industry has a major influence on achieving these goals by preserving intrinsic (chemical and sensory properties) and modifying extrinsic (food packaging and other external information) food attributes that can influence purchasing decisions. This article is a literature review of studies that analyse the influence of intrinsic and/or extrinsic attributes on consumer product preference and purchasing decisions.